PENGELOLAAN KEMANDIRIAN TERHADAP ANAK AUTIS DI DALAM KELUARGA - Nufusila, Destha Purwa; Khotimah, Khusnul (Universitas Tanjungpura, 2026)
This study aims to identify approaches, factors, and strategies for managing the independence of children with autism within the family environment through a Systematic Literature Review (SLR). The thematic synthesis method was used to examine and integrate findings from five empirical studies published between 2021 and 2023. The analysis focused on family-based management in developing daily living skills in children with Autism Spectrum Disorder (ASD). The synthesis revealed four main themes: behavioral strategies to promote independence, parental involvement, supporting and inhibiting factors, and outcomes of children's skill development. The behavior-based approach has proven effective when consistently implemented at home with parent training. Active family involvement is a key success factor because it allows for the implementation of concrete routines that strengthen children's adaptive abilities and self-confidence. Professional support, both through in-person and telehealth training, plays a crucial role in maintaining intervention consistency. Despite barriers such as time constraints, emotional stress, and limited resources, family-based independence management continues to have a positive impact on the adaptive functioning and well-being of children and families. This study emphasizes the need to develop contextual and sustainable intervention programs tailored to the socio-cultural characteristics of Indonesian families.